4 Financial Distress Models For Analysis Of Companies Before And During The Covid-19 Pandemic: Surveys In Automotive Companies In Indonesia - et. al., Andina Nur Fathonah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is undeniable that the influence of Covid-19 has hit all directions, from upstream to downstream. One of the sectors that has really felt the impact of Covid-19 is the automotive sector, especially since the implementation of the PSBB. Automotive manufacturers must close their production facilities as long as the government has not granted a permit. This is in line with the weakening public purchasing power for automotives. It took a long time for the automotive industry to emerge from the slump of this pandemic